Analysis of the Use of English in Slang on Video Content Used by Tiktok Content Creators - Nabila Maghfira; Savira Dwi Pratiwi (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2022)
One of the dynamics of language use that appears on social media today is the use of slang or slang as a reflection of current language developments. This phenomenon is interesting to talk about, especially the purpose of using slang or why slang is widely used when using social media. The data source for this research is the verbal form found on TikTok social media. This method uses three research stages: the data collection stage, the data analysis stage and the presentation stage of the data analysis results. At the data collection stage, we chose the observation method based on descriptive variables because, in this study, the researcher identified the use of English in social media, especially Tiktok. This method is used during data collection with note-taking techniques, especially slang. The data source in this research is video content. The data comes from several videos on Tiktok related to the slang used by content creators. The analysis results show that slang is used for various purposes, mainly as humorous material, to make it look different and contemporary. It helps facilitate social relations, reduce conversation seriousness, and encourage deep intimacy. Other purposes include showing off, avoiding gossip, and doing something sneaky.